The Role of Intelligence in Countering Terrorism in Poso Regency - Ida Lestiawati (Universitas Muhammadiyah Palu, 2023)
The results of this study indicate that the role of Intelligence, in this case, the Poso Police Intelligence apparatus in early warning early detection, has been able to carry out its duties and authorities to reduce or minimize security disturbances in society. This can be seen in the death of 5 terrorist DPO in Poso. ( five ) people in the 2021-2022 period. These efforts are carried out in several types of early detection activities. How to Identification, Fingerprint, Modus operandi, Files, Informants, Interrogations, and Scientific Assistance. These methods are used to detect perpetrators of criminal acts of terrorism to find perpetrators of crimes. The Intelligence function in deradicalizing former terrorism is undoubtedly needed so that the spread and development of terrorism can be minimized. The author suggests that the intelligence function in carrying out early detection in anticipating the threat of terrorist interference that occurs, it is best if the intelligence report provided to the leadership must be truly accurate and not made up so that the law can account for it.